CALIDAD DE Servicio brindado por parte del U.P.C., sector Pueblo Nuevo de la Provincia de Los Ríos - Huacon, Steven (2019)
The research carried out in the Community Police Unit of the Pueblo Nuevo Parish, aims to identify the quality of service provided by police officers belonging to the institution, because they are responsible for protecting the safety of citizens to improve the quality of life as part of the purpose of its creation. The study that determined a series of aspects related to the exposed variable, through the application of investigative instruments that provided information on the lack of internal control towards the gendarmes of the activities carried out during the workday, lack of knowledge training administrative and attention to citizens, factors that are reflected in the disagreement of the users who perceive the service